1997
DOI: 10.1530/jrf.0.1100249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cGMP and the nitric oxide donors glyceryl trinitrate and sodium nitroprusside on contractions in vitro of isolated myometrial tissue from pregnant women

Abstract: The purpose of this study was to determine the relaxant effects in vitro of two nitric oxide donors, glyceryl trinitrate and sodium nitroprusside, which are currently available for use in vivo, on contractions of non-labouring myometrium from pregnant women. Since nitric oxide also mediates relaxation by increasing the concentration of cGMP, sensitivity to 8-bromo-cGMP (a cGMP analogue) was also determined. The effects of the K(+)-channel opener lemakalim and of the Ca(2+)-channel blocker nifedipine were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 2 publications
2
25
1
Order By: Relevance
“…11,12) The involvement of NO as a major actor of cervical ripening would be consistent with the fact that cervical softening occurs during pregnancy, far before uterine contractions. This may also explain why cervical ripening induced by anti-progesterone is not prevented by COX-inhibitors.…”
Section: Blood Vessel Decorinsupporting
confidence: 55%
“…11,12) The involvement of NO as a major actor of cervical ripening would be consistent with the fact that cervical softening occurs during pregnancy, far before uterine contractions. This may also explain why cervical ripening induced by anti-progesterone is not prevented by COX-inhibitors.…”
Section: Blood Vessel Decorinsupporting
confidence: 55%
“…GTN, a nitric oxide donor, has been shown to produce a significant decrease in the contractility of human myometrium in pregnant and non-pregnant women in vitro (7)(8)(9)(10). In 1994, Lees et al (11) reported that transdermal nitroglycerin patches suppressed uterine contractions in all 20 episodes of preterm labor that occurred in 13 consecutive women enrolled in a pilot study, and they hence suggested that this nitric oxide donor could be an effective and safe tocolytic agent.…”
Section: Discussionmentioning
confidence: 99%
“…These agents stimulate the endothelial cell to produce and release NO, which in turn acts on the SMC to increase cGMP production. The ability of NO to relax SM has been described in multiple models and muscle types, including tracheal smooth muscle (Jia et al, 1995;Kannan and Johnson, 1995;Ward et al, 1995;Sadeghi-Hashjin et al, 1996;Yamakage et al, 1996), vascular smooth muscle (Landgraf et al, 1986;White et al, 1995;Moro et al, 1996;Olson et al, 1997), and myometrium (Buhimschi et al, 1995;Kuenzli et al, 1996;Nakanishi et al, 1996;Norman et al, 1997;Hennan and Diamond, 1998).…”
Section: Guanylate Cyclasesmentioning
confidence: 99%